Problematizando aspectos da nutrição e alimentação saudável em um guia didático investigativo - Mendonça, Carlos Roberto de (2022)
The present work was developed to enrich the learning of health issues witin Biology Education specifically addressing nutrition and school meals. We were motivated by the issue of food insecurity to investigate the concept of healthy eating and how firstyear high school students saw themselves as participants in this process. For the construction of the project, we worked on inquiry based teaching, providing students with the search, through discussions and oriented research based on guiding questions, allowing them to experience the Scientific Method and the Problematization Methodology. The proposed activities allowed students to raise hypotheses and seek answers using research that allowed them to have contact with the knowledge already produced on the subject, and based on them, they built their positions on healthy eating and its implications in the environment where they live. The students worked in groups, had the opportunity to propose menus for the school and finally, created comics, where they dealt with the importance of nutrition, facilitating their awareness about healthy eating and the setting of contents related to nutrition in a way that allowed to build an interesting didactic tool for other Biology teachers.